2013
DOI: 10.1017/s0033291713000871
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical psychotic experiences and bipolar spectrum features in depression: association with outcome of psychotherapy

Abstract: Background. Subthreshold psychotic and bipolar experiences are common in major depressive disorder (MDD). However, it is unknown if effectiveness of psychotherapy is altered in depressed patients who display such features compared with those without. The current paper aimed to investigate the impact of the co-presence of subclinical psychotic experiences and subclinical bipolar symptoms on the effectiveness of psychological treatment, alone or in combination with pharmacotherapy.Method. In a naturalistic study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 63 publications
4
46
0
Order By: Relevance
“…However, more research on underlying mechanisms is 13 required. The results of the present study show that PE serve as an indicator of illness severity and poor outcome in persons with non-psychotic psychopathology, in line with previous research (Guloksuz et al, 2015;Kelleher et al, 2012b;Perlis et al, 2011;Wigman et al, 2012;Wigman et al, 2014). Therefore, assessment of PE in individuals with non-psychotic psychopathology should be incorporated both in clinical practice and in future research, as previously suggested (Kelleher et al, 2013), in order to identify individuals at risk of suicidal behaviour.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, more research on underlying mechanisms is 13 required. The results of the present study show that PE serve as an indicator of illness severity and poor outcome in persons with non-psychotic psychopathology, in line with previous research (Guloksuz et al, 2015;Kelleher et al, 2012b;Perlis et al, 2011;Wigman et al, 2012;Wigman et al, 2014). Therefore, assessment of PE in individuals with non-psychotic psychopathology should be incorporated both in clinical practice and in future research, as previously suggested (Kelleher et al, 2013), in order to identify individuals at risk of suicidal behaviour.…”
Section: Discussionsupporting
confidence: 89%
“…PE were identified as a risk factor for several mental health outcomes including both psychotic (Kaymaz et al, 2012;Linscott and van Os, 2013) and non-psychotic psychopathology (Kelleher et al, 2012b) and are associated with increased treatment use and need for care in general population samples (Murphy et al, 2012). Moreover, PE serve as an indicator of illness severity and poor outcome in persons with non-psychotic psychopathology (Guloksuz et al, 2015;Kelleher et al, 2012b;Perlis et al, 2011;Wigman et al, 2012;Wigman et al, 2014) A recent meta-analysis reported that general population individuals with PE had an increased risk of both suicidal thoughts (i.e. suicidal ideation or suicidal plans) and suicidal behaviour (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the presence of psychotic experiences has a negative impact on recovery. In fact, previous evidence suggests lower responses to conventional psychological therapies in people with CMD-P (Perlis et al, 2011;Valiji Bharmal, Goodyer, & Wilkinson, 2015;Wigman et al, 2014). The IAPT programme does not routinely measure psychotic experiences or offer specific treatment to people who have them.…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan-Meier survival analysis was also used alongside a Cox proportional hazards regression in one study (Chopra et al, 2008). A point bi-serial correlation was conducted as the main analysis by Harkness et al (2014) and a logistic regression was conducted by Wigman et al (2014) and Segal et al (1999). The samples used in Chopra et al (2008) and Fresco et al (2007) were derived from the study by Segal et al (2006).…”
Section: Study Characteristicsmentioning
confidence: 99%